RELAÇÃO ENTRE EXPOSIÇÃO OCUPACIONAL A SOLVENTES ORGÂNICOS E ESTRESSE OXIDATIVO EM TRABALHADORES EXPOSTOS NA REGIÃO OESTE DE SANTA CATARINA: RELATIONSHIP BETWEEN OCCUPATIONAL EXPOSURE TO ORGANIC SOLVENTS AND OXIDATIVE STRESS IN EXPOSED WORKERS IN THE WEST REGION OF SANTA CATARINA - Boff, Everton; De Bona, Maristela (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Exposure of workers exposed to organic solvents (mainly benzene, toluene and xylene) is a constant problem for gas station workers. Brazilian legislation has many standards (and their annexes), ordinances, normative instructions and service orders that aim to protect those exposed and the environment to the vapors of these substances. Among these solvents, there is benzene, which is considered the most carcinogenic. In the present study, blood and urine samples of gas station attendants in the western region of SC were evaluated, which were divided into two groups, the “exposed” and “non-exposed”, being people who performed other activities. In the “exposed” group, the mean levels of trans, trans-muconic acid in the urine was 0.0547mg/g of creatinine (SD±0.00349), while in the “non-exposed” group it was less than 0.05mg. Urinary values are considered normal when less than 0.05mg/g of creatinine. Using non-parametric statistics, through independent samples of the Mann-Whitney U test, p=0.16 was obtained, with no difference between both groups. It was observed that the results obtained from this research showed no significant difference in causing oxidative stress.Referring to the ALA-D analyses, the results were between 39 and 49 µL for both the “exposed” and the “non-exposed” groups. Thus, we can state that ALA-D cannot serve as a biomarker for exposure to automotive fuels.